Statistical Inference. - Goldgerg, Samuel; Griffin, Charles H. (The Accounting Review, 1967)
Reviews the book "Statistical Inference," by Clifford H. Springer, Robert E. Herlihy, Robert T. Mall and Robert I. Beggs.